Exploring «the rift». Representations of divisions and social conflict in members of urban petty bourgeoisie - Artese, Matías (Universidad Nacional del Litoral, 2019)
In this article we explore the notions about conflict and social divisions in current Argentina, its causes and consequences. Through the realization of some interviews, these notions were worked with 13 small entrepreneurs in the metropolitan region of Buenos Aires. The objective is to know the elements that give form to the concept of «la grieta» (the crack), which is part of the current public agenda, driven through the hegemonic media. We try to elucidate a knowledge that in principle appears fragmentary and contradictory